Improved Vigenere approach incorporating pseudorandom affine functions for encrypting color images - El Bourakkadi, Hamid; Chemlal, Abdelhakim; Tabti, Hassan; Kattass, Mourad; Jarjar, Abdellatif; Benazzi, Abdelhamid (Institute of Advanced Engineering and Science, 2024)
This article presents an improvement to the traditional Vigenere encryption method, specifically adapted for the encryption of color images. This enhancement relies on the use of two chaotic maps widely employed in the field of cryptography. After vectorizing the original image and calculating the initialization value, which alters the seeding pixel to trigger the encryption process, our approach integrates two new large substitution tables. These tables are linked to confusion and diffusion functions, incorporating multiple reversible pseudo-random affine functions at the pixel level. Finally, a global permutation is applied to the entire resulting vector to increase the temporal complexity of potential attacks on our system. Simulations conducted on a diverse set of images of various sizes and formats demonstrate the resilience of our approach against any unexpected attacks.